Comparison of endometrial cancer risk in patients with endometrial precancerous lesions: WHO 1994 vs EIN classification. (19th May 2022) - Kender Erturk, Nergis; Basaran, Derman; Salman, Coskun
Abstract: Our aim was to investigate the frequency of concurrent endometrial cancer in patients with endometrial precancerous lesions (PCLs) using World Health Organization 1994 (WHO94) and endometrial intraepithelial neoplasia (EIN) systems. We retrospectively investigated patients that underwent surgery for endometrial PCLs according to WHO94 or EIN systems at Hacettepe University Gynecology Clinic between January 2002 and June 2014. Of the 267 patients, 189 (70.9%) were in the WHO94 group, 78 (29.2%) were in the EIN group. Mean age of patients was 50.2 years. Sixteen patients (8.5%) in WHO94 group and 15 (%19.2) patients in the EIN group had EC (p = 0.013). In WHO94 group, EC rate in patients with atypical EH (32.6%) was significantly more than patients with non-atypical EH (1.4%) ( p  < .001). Atypical EH and EIN are actual PCLs which could be accompanied by EC. Therefore, atypical EH and EIN should be treated surgically if there is no desire for fertility. IMPACT STATEMENT: What is already known on this subject? Endometrial hyperplasias are precursors lesion in the pathogenesis of endometrium adenocarcinomas. There are two classification systems: World Health Organization System and endometrial intraepithelial neoplasia system (WHO and EIN). What do the results of this study add? In this paper, we report on endometrial precancerous lesions. Controversy continues over the endometrial precancerous lesion classification. We also share our experiences in this regard. We concluded that the EIN system was superior in determining concurrent cancer risk. What are the implications of these findings for clinical practice and / or further research? The paper should be of interest to readers in the areas of gynecology.It is important to clarify the classifications of precancerous lesions in order to guide clinicians in the treatment of patients with endometrial precancerous lesions. In this context, it could be suggested to use the EIN system more widely.